Diseminasi Teknologi Pembelajaran Berbasis Inklusivitas dan Deep Learning dengan Media Digital Canva, Flipbook, dan Ispring Suite Menggunakan Model UTAUT - Dede Supriyanto; Yunus Abidin; Dede Trie Kurniawan; Cahya, Aulia Ihza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research investigates the factors influencing the adoption of digital teaching materials based on inclusiveness and deep learning using Canva and Heyzine flipbook, guided by the UTAUT model. The study aims to identify key determinants that affect teachers’ and students’ behavioral intentions and actual usage of digital media in inclusive educational settings. A quantitative approach was employed through surveys involving 120 participants from inclusive schools, with data analyzed using multiple linear regression to examine the influence of performance expectancy, facilitating conditions, and social influence. Results show that all three variables significantly impact behavioral intention, with performance expectancy being the most dominant predictor (β=0.48, p<0.01). The model explains 87% of the variance in behavioral intention (R²=0.87). These findings highlight that perceived benefits, infrastructural support, and social environment are critical for successful adoption of inclusive digital learning media. The study provides practical insights for educators and policymakers to strengthen strategies that promote technology acceptance in inclusive education. Limitations include sample scope and cross-sectional data, suggesting the need for longitudinal and mixed-methods research in future studies.